Soil Dynamic Properties Assessment By Using Geophysical Methods - Salleh, Alyaa Nadhira (2021)
Soil dynamic properties are the most critical geotechnical property of soils, help in the stability of structures on or below the earth. The information on soil properties can be used in the preliminary design of the foundation. Conventionally, the geotechnical method is used in assessing the dynamic properties of soil. However, this method consumes much time to get the result. Thus, this research utilises geophysical methods to investigate the soil dynamic properties of various lithology types via the application of the electrical resistivity method (ERM), seismic refraction (SR), and multichannel analysis of surface wave (MASW) methods.USM, Gelugor, and Paya Terubong were selected as a site of interest as there had been few cases of foundation failure in the past. USM comprises SAND and sandy SILT with resistivity values of 1754 – 2182 Ω.m and 90 – 1938 Ω.m. Paya Terubong comprises silty SAND and weathered granite with resistivity values of 40 – 380 Ω.m and 400 – 1800 Ω.m. Gelugor with resistivity values < 200 Ω.m for the saturated zone, 140 – 824 Ω.m for the weathered zone, and hard layer with a resistivity value of > 3000 Ω.m. The soil dynamic results show Paya Terubong has the most competent subsurface with 113 – 856 kPa for Qa. Gelugor with 72 – 462 kPa for Qa, while USM has the slightest bearing capacity values with < 200 kPa for Qa. Any subsurface with Qa values < 200 kPa is not suitable to support any type of building foundation. The Qa values have been established based on soil type; sandy SILT is less than 200 kPa, silty SAND between 113 – 615 kPa, and highly weathered granite is more than 700 kPa